2017
DOI: 10.3945/ajcn.117.152736
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation has no effect on insulin sensitivity or secretion in vitamin D–deficient, overweight or obese adults: a randomized placebo-controlled trial

Abstract: Vitamin D supplementation has been proposed as a potential strategy to prevent type 2 diabetes. Existing clinical trials have been limited by short duration, low doses of vitamin D, variability in participants' vitamin D-deficiency status, and the use of surrogate measures of body composition, insulin sensitivity, and insulin secretion. To address existing knowledge gaps, we conducted a double-blind, randomized, placebo-controlled trial to investigate whether vitamin D supplementation that is provided in a suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
90
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 43 publications
3
90
2
Order By: Relevance
“…In a small group of healthy male volunteers ( n = 18), insulin sensitivity, measured using the clamp procedure, was similar after either calcitriol or placebo treatment, but these subjects had normal body weight and vitamin D levels . The findings of a recent randomized controlled trial conducted on subjects with overweight or obesity and with no history of diabetes and vitamin D deficiency contrast with our findings, showing no difference in insulin sensitivity measured with the use of a hyperinsulinemic‐euglycemic clamp and insulin secretion measured with the use of an intravenous glucose tolerance test after vitamin D supplementation compared to placebo, despite a significant increase in 25(OH)D concentrations in the vitamin D group. However, in our study, subjects showed a reduction in body weight following a hypocaloric diet, suggesting that supplementation with vitamin D may have a greater effect than lifestyle intervention alone in improving insulin sensitivity in vitamin D deficient subjects with obesity.…”
Section: Discussioncontrasting
confidence: 86%
“…In a small group of healthy male volunteers ( n = 18), insulin sensitivity, measured using the clamp procedure, was similar after either calcitriol or placebo treatment, but these subjects had normal body weight and vitamin D levels . The findings of a recent randomized controlled trial conducted on subjects with overweight or obesity and with no history of diabetes and vitamin D deficiency contrast with our findings, showing no difference in insulin sensitivity measured with the use of a hyperinsulinemic‐euglycemic clamp and insulin secretion measured with the use of an intravenous glucose tolerance test after vitamin D supplementation compared to placebo, despite a significant increase in 25(OH)D concentrations in the vitamin D group. However, in our study, subjects showed a reduction in body weight following a hypocaloric diet, suggesting that supplementation with vitamin D may have a greater effect than lifestyle intervention alone in improving insulin sensitivity in vitamin D deficient subjects with obesity.…”
Section: Discussioncontrasting
confidence: 86%
“…Several intervention trials with vitamin D supplementation failed to show significant protection against the onset of diabetes [15][16][17] or improvement of cardiovascular risk, insulin sensitivity and glucose regulation. [18][19][20][21][22] As only 2 of these trials had a vitamin D deficiency (a 25-hydroxyvitamin D [25(OH)D] below 50 nmoL/L) as inclusion criterion, 19,20 more research is needed to draw conclusions about the association between vitamin D deficiency and type 2 diabetes. Studies on the effects of metformin on vitamin D levels are sparse.…”
mentioning
confidence: 99%
“…However, the definitive association between vitamin D and T2DM has also been doubted (16,17). Additionally, some Mendelian randomization studies and randomized placebo-controlled trials have challenged the causal association between vitamin D and T2DM (18)(19)(20)(21). (22,23).…”
Section: Discussionmentioning
confidence: 99%